Rollerball - Caan, James; Houseman, John.; Adams, Maud.; Beck, John.; Gunn, Moses, 1929-; Hensley, Pamela; Trentham, Barbara; Richardson, Ralph, Sir, 1902-; Jewison, Norman, 1926-; Harrison, William, 1933- (Santa Monica, Calif : MGM Home Entertainment, 2000)
In the perfectly controlled society of the 21st century, the only outlet for violence is a deadly spectator sport-- Rollerball.
VHS format.
In stereo ; digital video transfer.
Closed captioned for the hearing impaired.
Originally produced as a motion picture in 1975.
Producer/director, Norman Jewison ; screenplay, William Harrison ; music, Andre Previn.
James Caan, John Houseman, Maud Adams, John Beck, Moses Gunn, Pamela Hensley, Barbara Trentham, Ralph Richardson.
Keywords: Science fiction films; Feature films; Violence in sports -- Drama -- Video recordings; Violence in popular culture -- Drama -- Video recordings; Video recordings for the hearing impaired